2013
DOI: 10.12720/jolst.1.1.47-50
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Food and Feeding Habits of Mullet Fish, Liza Subviridis (Valenciennes, 1836), Valamugil Buchanani (Bleeker, 1853) from Merbok Estuar

Abstract: The present study was conducted to identify the type of food taken by mullet fish. To study the food and feeding habits, a total of 80 fish samples were collected from upper zone of Merbok estuary. Two methods were followed, namely occurrence and numerical for the analysis of gut contents. The observation identified algae, diatoms, desmids, plant materials, annelids, crustaceans, fishes, detritus and sand grains as major food items. Plant materials were the most abundant food items by numerical and occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
1
14
0
1
Order By: Relevance
“…Results similar to the present study have been reported by Chan and Chua (1979), Prapaporn et al (1998) in Thachin Estuary, Thailand and Fatema et al (2013) in Merbok Estuary of Peninsular Malaysia. Studies in Mugil cephalus also observed preference for diatoms (Tandel et al, 1986;Khan and Fathima, 1994;Rao and Sivani, 1996;Bekova et al, 2013;Rao and Babu, 2013;Modou et al.…”
Section: Weight Of the Gutsupporting
confidence: 93%
“…Results similar to the present study have been reported by Chan and Chua (1979), Prapaporn et al (1998) in Thachin Estuary, Thailand and Fatema et al (2013) in Merbok Estuary of Peninsular Malaysia. Studies in Mugil cephalus also observed preference for diatoms (Tandel et al, 1986;Khan and Fathima, 1994;Rao and Sivani, 1996;Bekova et al, 2013;Rao and Babu, 2013;Modou et al.…”
Section: Weight Of the Gutsupporting
confidence: 93%
“…The tropic behavior of mullets has been reported by different authors using extensive terminology which categorized feeding patterns of these species [9]. Some examples include algae feeders [11], micro and meio-benthos feeders [12], interface-feeders [13], deposit feeders [14], benthic microphagous omnivores [15] and limnobenthofagous [16].…”
Section: Introductionmentioning
confidence: 99%
“…There is less information on the feeding habit of mullet fish in Malaysia especially on Merbok River estuary (Mansor et al 2012, Fatema et al 2013a. Therefore, this study was undertaken to assess the monthly and seasonal variation of food items in the stomachs of two mullet fish species (Chelon subviridis, Valamugil buchanani ) which may provide some input in relation to the habitat of these fish species.…”
Section: Introductionmentioning
confidence: 99%